Research on a Mobile Malicious Code Management and Control Method Based on Cloud-Pipeline-Terminal - Jun Li (Dianxin kexue)
In order to solve the increasingly serious security issues caused by malwares in mobile internet,a“cloud-pipeline-terminal”model was proposed to implement detection and killing of mobile internet malwares.The proposed model composes of a cloud computing platform to support the analysis and measurement of the malwares and to implement strategy distribution and management of the system,a monitoring and intercepting system on the side of mobile communication pipelines and a terminal security application to check and kill the malwares.The purpose is to build a safe and harmonious mobile internet environment.